In varietate concordia?! Political parties' digital political marketing in the 2019 European Parliament election campaign. (March 2022) - Kruschinski, Simon; Bene, Márton
This article provides the first comprehensive analysis of how parties across 28 countries use digital political marketing on Facebook by drawing on the example of the 2019 European Parliament election. We introduce a theoretical model of political Facebook marketing and compare the paid media activity (sponsored posts, ads) of 186 parties to their owned media (posts) and earned media (user reactions, comments, shares). Our results concerning cross-country patterns indicate that differences in European parties' paid media activity exist and only a few parties leverage sophisticated targeting strategies. Regarding temporal dynamics, we find that paid media is used to supplement owned media during similar campaign phases. In terms of engagement-triggering effects, we show that sponsoring posts is a suitable tool to increase earned media. Overall, paid media activity on Facebook is largely embedded into parties' overall marketing strategy and national countries' regulatory settings. Our results have implications for the understanding of public opinion, voting behaviour and the regulations of elections in modern European democracies.